Reactive Nodular Fibrous Pseudotumor: Case Report and Review of the Literature. (30th March 2014) - Salihi, Rawand; Moerman, Philippe; Timmerman, Dirk; Van Schoubroeck, Dominique; Op de beeck, Katya; Vergote, Ignace
Abstract : We will describe a case of a patient diagnosed with a rare identity of a benign lesion, "reactive nodular fibrous pseudotumor" (RNFP). It is a tumor which preoperatively can present as a malignant tumor and is only reported in 19 cases. According to the very limited amount of information on this tumor in the literature it is mostly seen after trauma or intraperitoneal inflammation. Our case is the second one of RNFP associated with endometriosis, which is a frequently seen intraperitoneal inflammation process in women. Knowledge that these large pseudotumoral lesions can occur is important to direct the management of these patients.